Ultra-processed foods intake and sex hormone levels among children and adolescents aged 6–19 years: a cross-sectional study - Zhao, Hao; Gui, Wei; Liu, Shangtao; Zhao, Fangyu; Fan, Wenyan; Jing, Fangyuan; Sun, Chuan (Frontiers in Nutrition, 2024)
Background: Sex hormones are crucial for the development of children and adolescents. The increasing consumption of ultra-processed foods (UPFs) among children and adolescents in the U.S. has raised concerns about their potential impact on health, including hormonal balance. Methods: Data from 3,354 participants aged 6-19 years from the NHANES 2013–2016 were analyzed. UPFs intake was categorized using the NOVA food classification system, and the percentage of total daily energy intake from UPFs was calculated. Serum levels of total testosterone (TT), sex hormone-binding globulin (SHBG), and estradiol (E2) were measured. The free androgen index (FAI) and TT/E2 ratio were calculated to estimate bioavailable testosterone levels and the balance between androgens and estrogens, respectively. Multiple linear regression models adjusted for potential confounders estimated the associations. Results: Our results showed that higher intake of UPFs was marginally associated with decreased serum SHBG levels (Quartile (Q) 2 vs. Q1: β=-5.3%, 95% confidence interval (CI): -17.0%, 8.1%; Q3 vs. Q1: β=-14.6%, 95%CI: -25.1%, -2.5%; Q4 vs. Q1: β=-9.0%, 95%CI: -20.3%, 3.8%; P trend=0.081), and significantly associated with increased serum FAI in female adolescents (Q2 vs. Q1: β=3.2, 95%CI: -3.3, 9.7; Q3 vs. Q1: β=7.6, 95%CI: -0.7, 16.0; Q4 vs. Q1: β=9.5, 95%CI: 1.5, 17.6; P trend=0.019). Additionally, UPFs intake showed a marginal positive association with increased serum SHBG levels (P trend=0.057) in male children and FAI (P trend=0.150) in male adolescents, respectively. Similar results were observed when participants were stratified by puberty status, except for the association between UPFs intake and SHBG in male children. However, there were no associations between UPFs consumption and TT, E2, or the TT/E2 ratio both in males and females. Conclusion: Higher UPFs consumption is associated with increased FAI in adolescents, particularly in females, indicating higher bioavailable testosterone levels. Future studies should validate these findings with direct free testosterone measurements and more precise dietary intake assessments.